2022
DOI: 10.3389/fcvm.2022.922858
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of thromboembolic complications after stent-assisted coiling of acutely ruptured intracranial aneurysms: A retrospective multicenter study

Abstract: BackgroundStent-assisted coiling (SAC) has been reported to safely and effectively treat wide-necked unruptured intracranial aneurysms. However, SAC of acutely ruptured aneurysms is controversial because of perioperative thromboembolic complications. We aimed to investigate the predictors of the thromboembolic complications after SAC of acutely ruptured aneurysms.MethodsWe performed a retrospective multicenter analysis of 110 consecutive patients with ruptured intracranial aneurysms treated with SAC within 72 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Furthermore, it has been suggested that wide-necked aneurysms are more amenable to stentassisted embolization. Several studies have suggested that the dometo-neck ratio has an impact on perioperative TEs during stent-assisted embolization of ruptured intracranial aneurysms (Li et al, 2022). Additionally, Liu et al reported that an increase in the dome-to-neck ratio is associated with a higher likelihood of perioperative thromboembolic events during stent-assisted embolization of ruptured intracranial aneurysms, although the association was not significant (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it has been suggested that wide-necked aneurysms are more amenable to stentassisted embolization. Several studies have suggested that the dometo-neck ratio has an impact on perioperative TEs during stent-assisted embolization of ruptured intracranial aneurysms (Li et al, 2022). Additionally, Liu et al reported that an increase in the dome-to-neck ratio is associated with a higher likelihood of perioperative thromboembolic events during stent-assisted embolization of ruptured intracranial aneurysms, although the association was not significant (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, a multicenter retrospective study suggested that the prevention of perioperative TEs using intravenous tirofiban was less effective than when using a preoperative oral loading dose of DAPT. This could be due to the small sample size, with only 15 cases in the tirofiban group, making the study somewhat subject to error (Li et al., 2022 ). We further analyzed the postoperative 24‐h coagulation indexes and venous blood platelet counts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation